Some Investigations on Protease Enzyme Production Kinetics Using Bacillus licheniformis BBRC 100053 and Effects of Inhibitors on Protease Activity - Zahra Ghobadi Nejad; Soheila Yaghmaei; Nazanin Moghadam; Bahareh Sadeghein (International Journal of Chemical Engineering)
Due to great commercial application of protease, it is necessary to study kinetic characterization of this enzyme in order to improve design of enzymatic reactors. In this study, mathematical modeling of protease enzyme production kinetics which is derived from Bacillus licheniformis BBRC 100053 was studied (at 37°C, pH 10 after 73 h in stationary phase, and 150 rpm). The aim of the present paper was to determine the best kinetic model and kinetic parameters for production of protease and calculating Ki (inhibition constant) of different inhibitors to find the most effective one. The kinetic parameters Km (Michaelis-Menten constant) and Vm (maximum rate) were calculated 0.626 mM and 0.0523 mM/min. According to the experimental results, using DFP (diisopropyl fluorophosphate) and PMSF (phenylmethanesulfonyl fluoride) as inhibitors almost 50% of the enzyme activity could be inhibited when their concentrations were 0.525 and 0.541 mM, respectively. Ki for DFP and PMSF were 0.46 and 0.56 mM, respectively. Kinetic analysis showed that the Lineweaver-Burk model was the best fitting model for protease production kinetics DFP was more effective than PMSF and both of them should be covered in the group of noncompetitive inhibitors.